Inulin and Its Application in Drug Delivery - Franklin Afinjuomo; Sadikalmahdi Abdella; Souha H. Youssef; Yunmei Song; Sanjay Garg (MDPI AG, 2021)
Inulin's unique and flexible structure, stabilization/protective effects, and organ targeting ability make it an excellent drug delivery carrier compared to other biodegradable polysaccharides. The three hydroxyl groups attached to each fructose unit serve as an anchor for chemical modification. This, in turn, helps in increasing bioavailability, improving cellular uptake, and achieving targeted, sustained, and controlled release of drugs and biomolecules. This review focuses on the various types of inulin drug delivery systems such as hydrogel, conjugates, nanoparticles, microparticles, micelles, liposomes, complexes, prodrugs, and solid dispersion. The preparation and applications of the different inulin drug delivery systems are further discussed. This work highlights the fact that modification of inulin allows the use of this polymer as multifunctional scaffolds for different drug delivery systems.